2007
DOI: 10.1002/sim.2890
|View full text |Cite
|
Sign up to set email alerts
|

Mapping disability‐adjusted life years: a Bayesian hierarchical model framework for burden of disease and injury assessment

Abstract: This paper presents a Bayesian disability-adjusted life year (DALY) methodology for spatial and spatiotemporal analyses of disease and/or injury burden. A Bayesian disease mapping model framework, which blends together spatial modelling, shared-component modelling (SCM), temporal modelling, ecological modelling, and non-linear modelling, is developed for small-area DALY estimation and inference. In particular, we develop a model framework that enables SCM as well as multivariate CAR modelling of non-fatal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
0
29
0
1
Order By: Relevance
“…Their sum was proposed to form a deviance information criterion which may be used for comparing models for their overall performances, in terms of balancing complexity and fit (Spiegelhalter et al, 2003a). It is noteworthy that in this and similar studies the DIC calculation has shown considerable stability over different MCMC runs, and we observed considerable consistency in the pD-Dbar-DIC assessments with respect to knot and model selections (MacNab, 2007;MacNab and Gustafson, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…Their sum was proposed to form a deviance information criterion which may be used for comparing models for their overall performances, in terms of balancing complexity and fit (Spiegelhalter et al, 2003a). It is noteworthy that in this and similar studies the DIC calculation has shown considerable stability over different MCMC runs, and we observed considerable consistency in the pD-Dbar-DIC assessments with respect to knot and model selections (MacNab, 2007;MacNab and Gustafson, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…Each informant was presented with sample datasets on a laptop computer and asked to provide comments on the data presented. Injury mortality and hospitalisation counts and rates, stratified by gender and based on 1991-2000 populationbased administrative data (MacNab, 2007), were presented in Excel spreadsheets for major causes of injuries. Estimates of years of life lost, healthy years lost due to disability and disability adjusted life years were derived from disability weight and duration figures developed in the Global Burden of Disease study of 1990, with a 3% annual discount rate and zero age weighting (Murray & Lopez, 1996;MacNab, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Injury mortality and hospitalisation counts and rates, stratified by gender and based on 1991-2000 populationbased administrative data (MacNab, 2007), were presented in Excel spreadsheets for major causes of injuries. Estimates of years of life lost, healthy years lost due to disability and disability adjusted life years were derived from disability weight and duration figures developed in the Global Burden of Disease study of 1990, with a 3% annual discount rate and zero age weighting (Murray & Lopez, 1996;MacNab, 2007). The informants were also presented with two sample maps comparing (using colour-coding) annual iatrogenic injury risk estimates for children and youth aged 1 to 19 years across health regions.…”
Section: Methodsmentioning
confidence: 99%
“…To accommodate these features, a multivariate extension of the prior of Leroux et al [12] is used [13], but adapted to include regression terms η qi as, for example, in the spatial priors of Bell and Broemeling [14] and Stern and Cressie [15]. Thus denote…”
Section: Incorporating Spatial Correlation In the Need Constructsmentioning
confidence: 99%